EFEK PENAMBAHAN DINDING GESER ATAU PERIMETER BEAMS TERHADAP PERILAKU DINAMIS STRUKTUR PELAT DATAR EMPAT TINGKAT - Sudarsana, I Ketut; Giri, Ida Bagus Dharma; Wiryadi, I Gede Gegiranang (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 18, No. 1, Januari 2014, 2016)
Flat plate structural system is a plate structural system that supported directly by columns without column heads or drop panels. The advantages of this system are distance between the floors can be shortened, faster construction, ease of architectural work and installation of Mechanical, Electrical and Plumbing Equipment (MEP). However, this system has a weakness on the join (connection of slab-column) that is too flexible and susceptible to punching shear failure especially when the existence of moment due to earthquake. This study investigates the changes on dynamic behaviors of flat plate structures when it is added lateral stiffeners such as shear walls or perimeter beams in terms of its natural period, base shear force, floor displacement, and a change on the forces of the structural elements. The structure of the building being simulated is regular structure consisting of 4 floors with 3 meter floor to floor space and 4 spans along X axis direction (Lx = 6 m) and 3 spans along Y axis direction (Ly = 5 m). The building is a hotel, which stands on medium soil in Bali Provice. Flat plate structures with additional of shear walls or perimeter beam are designed in accordance with the requirements of SNI 03-2847-2002. Analyses were performed in three dimensions (3D) using commercial software SAP2000 v15, where the three structure models have the same property namelyplate thickness, column dimensions, mass and material properties. Dynamic behaviorsare studied based on time history analysis (integration time step) according to the average acceleration method from Newmark with acceleration record of the El-Centro earthquake 1940. Analysis shows that addition of shear walls or perimeter beam causes the natural period of structure and horizontal displacement decrease, while the base shear force and structural rigidity increase. Moments, shear forces on columns and shear forces on the plate around the column decrease with the addition of shear walls. The addition of perimeter beam increases the moments and shear forces on first floor columns and shear forces on the plate around the column decrease dramatically on the edge columns
Keywords: Dynamic behavior, flat platestructures, shearwalls, perimeter beams